Perancangan Ontologi: Pendekatan Representasi Pengetahuan Topeng Bali - Gita, Ni Nyoman Sukma Prasetyadewi; Wirawan, I Made Widhi; Pramartha, Cokorda (Jurnal Nasional Teknologi Informasi dan Aplikasnya; Vol 2 No 4 (2024): JNATIA Vol. 2, No. 4, Agustus 2024DO - 10.24843/JNATIA.2024.v02.i04.p12, 2024)
This research aims to design an ontology model representing knowledge concerning Balinese masks, particularly focusing on their functions and uses. The methodology employed encompasses stages including specification, knowledge acquisition, conceptualization, integration, implementation, evaluation, and documentation. Implementation utilized Protégé software, resulting in 7 classes, 8 object properties, 5 data properties, and 26 instances related to Balinese Masks. Testing involved SPARQL queries to retrieve information on Balinese masks based on criteria such as function, motif, name, region, and artist. Test results demonstrate the efficacy of the ontology model in addressing relevant inquiries. This study seeks to offer information and digital documentation on Balinese masks, particularly regarding their function and use, thereby contributing to the preservation of this cultural heritage.